Evaluation of magnetic field from different power transmission line configurations in malaysia - Said I.; Rahman N.A.; Hussain H.; Farag A.; Juhana T. (2023)
Double circuit overhead transmission lines in Malaysia have been in operation for many years. Rapid infrastructure development prompted the utility company to enhance electrical transmission capacity to ensure adequate and reliable supply to the consumers. Due to this some towers had been erected close to another tower. In certain places, under different circumstances it could consists of six towers energized within the same land reserve. It is estimated that 80% from the total number of transmission line towers in Malaysia are of the double circuit type while the rest are designed for the quadruple circuit type. There is a requirement to study and evaluate the impact of EMF exposure levels for these multiple towers. This paper presents the results of magnetic field measurements at various transmission line configurations in Malaysia. Using the actual physical dimensions of the transmission lines, models were constructed and verified. Simulation studies were then performed and ground level magnetic field at the edge of right-of-way and maximum magnetic field for each case was tabulated. The studies indicate that for the same number of circuits and carrying the same load, up to 47% of maximum magnetic field reduction can be achieved with a 33% reduction in the width of right-of way if the quadruple,circuit tower configuration is used.